Effects of sleep deprivation on sports performance and perceived exertion in athletes and non-athletes: a systematic review and meta-analysis - Kong, Yan; Yu, Beibei; Guan, Guangming; Wang, Yang; He, Hui (Frontiers in Physiology, 2025)
BackgroundSleep deprivation can significantly affect sports performance and the perception of fatigue. However, the impact of sleep deprivation on sports performance remains a subject of ongoing debate across different populations.ObjectivesThis study aimed to investigate the effects of sleep deprivation on sports performance and ratings of perceived exertion (RPE) in different groups, as well as how different types of sleep deprivation affect these aspects.MethodsThis systematic review followed the PRISMA guidelines (PROSPERO CRD42023492792). Randomized controlled trials (RCTs) and randomized crossover studies published in any language or up to any date were eligible based on the P.I.C.O.S. criteria. The systematic search included databases such as PubMed, Cochrane, Embase, Web of Science, and EBSCO, covering studies up to September 2024. The Cochrane RoB 2 tool was used to assess the risk of bias. Meta-analysis was conducted using either a fixed-effect model or a random-effects model. This study conducted subgroup analyses based on different populations, types of sleep deprivation, and testing times.ResultsThis review includes 45 studies, comprising 16 on aerobic endurance (AE) performance, 8 on anaerobic endurance (AnE) performance, 23 on explosive power (EP), 10 on maximum force (MF), 4 on speed, 4 on skill control, and 12 on rating of perceived exertion (RPE). The results indicate that sleep deprivation significantly impaired AE in athletes [SMD = −0.66; 95% CI (−1.28, −0.04); P = 0.04], as well as EP [SMD = −0.63; 95% CI (−0.94, −0.33); P < 0.00001], MF [SMD = −0.35; 95% CI (−0.56, −0.14); P = 0.001], speed [SMD = −0.52, 95% CI (−0.83, −0.22); P = 0.0008], skill control [SMD = −0.87; 95% CI (−1.7, −0.04); P = 0.04], and RPE [SMD = 0.39; 95% CI (0.11, 0.66); P = 0.006]. Additionally, AE was also reduced in healthy non-athletes [SMD = −1.02; 95% CI (−1.84, −0.21); P = 0.01]. During the sleep deprivation process, early sleep deprivation (PSDE) significantly reduced EP [SMD = −1.04; 95% CI (−1.58, −0.5); P = 0.0002], MF [SMD = −0.57; 95% CI (−0.94, −0.19); P = 0.003], speed [SMD = −0.78; 95% CI (−1.35, −0.2); P = 0.008], and RPE [SMD = 0.6; 95% CI (0.17, 1.02); P = 0.006]. Late sleep deprivation (PSDB) impacted speed [SMD = −0.57; 95% CI (−1.15, 0.01); P = 0.05], skill control [SMD = −2.12; 95% CI (−3.01, −1.24); P < 0.00001], and RPE [SMD = 0.47; 95% CI (0.02, 0.92); P = 0.04]. Overall, total sleep deprivation primarily affected AE [SMD = −0.56; 95% CI (−1.08, −0.05); P = 0.03]. In terms of testing phases, p.m. tests had a significant impact on AE [SMD = −1.4; 95% CI (−2.47, −0.34); P = 0.01], EP [SMD = −0.68; 95% CI (−1.06, −0.31); P = 0.0004], MF [SMD = −0.3; 95% CI (−0.51, −0.09); P = 0.005], skill control [SMD = −2.12; 95% CI (−3.01, −1.24); P < 0.00001], and RPE [SMD = 0.72; 95% CI (0.20, 1.24); P = 0.007]. In contrast, a.m. tests primarily affected speed [SMD = −0.81; 95% CI (−1.52, −0.1); P = 0.03] and RPE [SMD = 0.44; 95% CI (0.01, 0.86); P = 0.04].ConclusionSleep deprivation significantly impairs athletes' performance across various domains, including AE, MF, speed, and skill control, while also exacerbating RPE. In contrast, although sleep deprivation also negatively affects the AE of healthy non-athletes. Furthermore, PSDE appears to have a more pronounced effect on sports performance overall. Additionally, performance assessments conducted in the p.m. have been shown to further impact sports performance. These findings are crucial for understanding how sleep deprivation impacts both athletes and non-athletes, particularly in the context of training and competitive settings.